Predict high school students' final grades using basic machine learning - Sugiyanto, Sigit (Journal of Applied Data Sciences, 2021)
To improve the quality of students, teachers must be able to take precautionary measures to deal with students who are lacking or have the potential to experience deficiency. Student ratings are temporary, however, have a profound impact on students' mental and enthusiasm for learning. As a teacher, it is very important to make predictions in dealing with this matter because if the ranking has been issued, it is too late. In this article, we will discuss and make Student grade predictions using basic machine learning, we will also discuss the continuity between student data and machine learning